(untitled) (Journal of University of Babylon for Engineering Sciences, 2022)
The growth in modernistic surgery is especially related to expansion of biomaterials. The interior fracture fixation devices, articular prostheses, vascular prostheses, and replace heart valves are models in this part. A great attention to the carbonaceous materials due to the strong potential biocompatibility, wear resistance ,good mechanical properties thus they are used for biomedical applications. All these properties available in pyrolytic carbon. It is a manmade material of carbon and not found in nature. It can be produced by chemical vapour deposition method for biomedical applications. Mechanical heart valves, orthopedic applications as hand and wrist implant made from pyrolytic carbon. This research is described method of production,properties, biomedical applications of pyrolytic carbon.